Edukasi Pemanfaatan Buah Pepaya (Carica Papaya L) terhadap Nafsu Makan Anak sebagai Upaya Pencegahan Stunting - Nurul Fatmawati; Yesvi Zulfiana; Irni Setyawati; Sri Handayani (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The toddler period (golden period) is a golden period that is very sensitive to the environment and this period is very short and cannot be repeated. Stunting is linear growth that fails to reach its genetic potential as a result of poor diet and infectious diseases. Many parents have difficulty dealing with the problem of lack of appetite in children. Drugs are always the first choice for this condition. Drugs that increase appetite in the long term cause other chronic diseases. Multivitamins in the form of fruits that have high nutritional value, taste sweet, are cheap and easy to obtain are Carica Papaya. The aim is to increase the knowledge of mothers under five about the benefits of papaya fruit (Carica Papaya) on appetite as an effort to prevent stunting. Based on the results of community service regarding Health Education Regarding the Utilization of Papaya Fruit (Carica Papaya) Against Children's Appetite as a Stunting Prevention Effort which was carried out on December 10, 2022. This community service activity went smoothly with the participation of 30 mothers with toddlers. The participants were very enthusiastic. As many as mothers have used papaya fruit (Carica Papaya L) as an appetite enhancer as an effort to prevent stunting.